Analisis Kepuasan Nasabah Gen Z dalam Menggunakan Aplikasi BSI Mobile - Fadhliah, Syifa; Putra, Purnama (ITB AAS INDONESIA Surakarta, 2024)
This study aims to analyze the variables of E-Service Quality, namely Fulfillment, Responsiveness, Compensation, Efficiency, System Availibility, Privacy, Contact on the satisfaction of Gen Z customers in using the BSI Mobile application. The method used is a quantitative method by distributing questionnaires as a data collection tool and multiple regression analysis tests are carried out through SPSS Statistic Version 26 Software. The population in this study is customers who belong to Generation Z and use the BSI Mobile application domiciled in Greater Jakarta. Sampling uses non-probability sampling by determining the number of samples using the Cochran formula which produces a sample number of 100 respondents. This study shows that the results of simultaneous tests for the variables of Fulfillment, Responsiveness, Compensation, Efficiency, System Availability, Privacy, and Contact together affect the satisfaction of Gen Z customers in using the BSI Mobile application. Then in the partial test for the variables Fulfillment, Responsiveness, Compensation, Privacy, and Contact, each had no effect and was not significant on the satisfaction of Gen Z customers in using the BSI Mobile application. This is because Gen Z customers have not felt the good quality of service from BSI regarding the fulfillment, response and communication of customer complaints and the security of customer personal data that has not been maximized. Meanwhile, the Efficiency and System Availability variables have a positive and significant effect on Gen customer satisfaction in using the BSI Mobile application. This research has recommendations for Bank Syariah Indonesia to continue to improve the quality of BSI Mobile services so that it can increase customer satisfaction in using it.